THE DECAY OF THE USE OF THE TERM “ABSTRACT CAUSE OF INVALIDITY” AND HOW CONSTITUTIONAL PRINCIPLES SURVIVE AN ELECTORAL PROCESS (Andamios, Revista de Investigación Social, 2010)
The essay analyses the creation, the nature and the development of the term known as election’s “abstract cause of invalidity”, as well as its apparent “death” due to the last constitutional reform made to the election law in Mexico in 2007. Some precisions are made on the subject of the validity of the constitutional principles and the diversity of interpretations that can be made around the punishment that comes with the violations of an electoral process.
Keywords: Abstract cause of invalidity; annulment of election results; federal electoral rights